Effect of biostimulation in the bioremediation of waters coming from debittering olives process - Maldonado, Mariela Beatriz (2022)
The potential bioremediation of native microorganisms presents in lye waters, produced during the industrial debittering of green table olives was studied in this work. Two treatments, T1 and T2, as well as the corresponding control were carried out, whilst the biostimulation method was evaluated under aerobic conditions. The evolution of parameters such as BOD5, COD, electrical conductivity and reducing sugars were measured, whereas the growth of native microorganisms was monitored by total plate count. COD parameter showed a decrease of 100% for both treatments, although electrical conductivity decreased around 35-30% in treatment T1 and 17–30 % in the treatment T2. The initial BOD5 decreased consistently with the reduction in COD. The controls only had aeration, however in absence of biostimulation, similar results were observed in all treatments, due to the growth of microorganisms stimulated by the native source of organic matter. However, biostimulation accelerated the process, especially in the reduction of pH, transforming the alkaline effluent into a more neutral effluent.